Advanced Encryption Techniques for Database Security in Cloud Environments - Sachin Gupta, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This technical article explores advanced encryption techniques for enhancing database security in cloud environments, addressing the growing need for robust data protection as organizations increasingly migrate to cloud-based solutions. The article covers encryption standards such as AES-256, RSA, and Elliptic Curve Cryptography, as well as key management approaches using Hardware Security Modules (HSMs) and Key Management Services (KMS). It also delves into cutting-edge concepts like homomorphic encryption and quantum-resistant algorithms. The discussion encompasses performance optimization strategies and regulatory compliance considerations, providing a comprehensive overview of the current state and future trends in cloud database security.
Keywords: Cloud Database Security; Encryption Techniques; Key Management; Homomorphic Encryption; Quantum-Resistant Algorithms